TWO-CHANNEL GRAVIMETER OF AVIATION GRAVIMETRIC SYSTEM - BEZVESILNA, OLENA; GRYNEVYCH, MARIIA; TOLOCHKO, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
A two-gyro gravimeter of the aviation gravimetric system is proposed and investigated, which provides higher measurement accuracy than known gravimeters, due to the elimination of errors from the cross angular velocities of the base and the angular velocity of the Earth’s rotation and the measurement of the full vector of the acceleration of gravity. To measure the acceleration of gravity, an AGS is proposed, which has greater accuracy and speed than known and consists of a three-stage gyroscope located in the inner and outer frames, equipped with interframe correction systems, which include an angle sensor (DC) located on the axis of the inner frame of the gyroscope and a torque sensor (DM) connected to its output is located on the axis of the outer frame. DM, located on the axis of the inner frame, is connected to the DC output. An additional, identical to the first, three-stage gyroscope, the rotor of which rotates in the opposite direction from the main gyroscope, is introduced in the AGS under consideration. The additional gyroscope of the AGS is also provided with similar correction systems, which consist of a DC located on the axis of the inner frame, and a DM located on the axis of the outer frame connected to its output, a DC located on the axis of the outer frame, to the output of which a DM located on the axis is connected inner frame The centers of gravity of two identical (main and additional) gyroscopes are shifted by the same distance in one direction along the axes of rotation of the rotors of the gyroscopes relative to the axes of the outer frames. The vectors of the kinetic moments of the two gyroscopes are oppositely directed. In the two-channel gravimeter, two output signals of linear acceleration are formed as the sum of signals from DC of two gyroscopes relative to one z-axis and as the sum of signals from DC of two gyroscopes relative to the second x-axis. The output signals are fed to the computer. Both gyroscopes of the system’s gyrogravimeter are mounted on a platform whose angular position is controlled by a motor (DV) installed on the x-axis and a DV on the z-axis. Both motors control the angular position of the platform by signals. The computer also receives signals from the system for determining navigation parameters and from the height meter.